Gamified Investment Apps and the Principle of Neutrality: A Comparative Legal Analysis of In-App Rewards and Badges in Indonesia, Malaysia, and the Philippines - Lu Sudirman; Nadia Carolina Weley; Michael T. Sacramed; Antony Antony; David Tan (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
This study aims to examine whether in-app rewards and badges in investment applications constitute inducements or remain neutral engagement features, while assessing the adequacy of the legal frameworks in Indonesia, Malaysia, and the Philippines in addressing this issue. The research employs a doctrinal legal method with a comparative approach, analyzing statutes, regulations, and legal principles related to investment law, consumer protection, and financial services regulation in the three jurisdictions. The study also draws on relevant literature concerning gamification, investor behavior, and digital financial services to identify the normative position of app-based rewards and badges within the broader legal context. The findings show that in-app rewards and badges are not inherently neutral because they are designed to increase engagement, usage frequency, and trading activity among users. Although these features are not necessarily unlawful, they may function as subtle behavioral inducements that influence investor decision-making, particularly among novice retail investors. The comparative analysis reveals that the Indonesian legal framework contains limited and indirect provisions that may apply to such features, but it lacks a specific principle of neutrality for investment app design. Malaysia provides relatively broader consumer and capital market protections, yet still does not expressly regulate gamified inducements in investment apps. The Philippine framework similarly focuses on misleading statements and disclosure obligations, leaving a gap in addressing psychological manipulation through gamification. Overall, the study finds that the current legal frameworks in all three countries are not fully equipped to regulate the subtle but potentially harmful effects of gamification in investment applications. Therefore, the study recommends the incorporation of a limited neutrality principle for investment app providers, especially regarding features that may operate as inducements rather than genuine engagement tools.